Corporate Social Responsibility as a Tool to Increase Happiness Among Workers in an Organization - Wolf, Ruth (Prabandhan: Indian Journal of Management, 2013)
Organizations today devote a great deal of resources to applying a ’positive psychology’ approach in the workplace. Many studies point out that it is possible to increase employee motivation and make work in the company more efficient, and it has been demonstrated that the principles of positive psychology reinforce this approach. CSR (Corporate Social Responsibility) is an important factor in strengthening an employee’s positive outlook, as it requires him to involve himself in giving and contributing to the community, provides personal fulfillment and can increase his satisfaction at work. Today more than ever, the positive influence of organizations and business on the community is emphasized. The phenomenon of CSR is well-known and has expanded activities across the entire world. Organizations and companies today increasingly understand that the act of giving to another also has a personal and business value for the contributing workers within the organization as well as for the community, just as the positive psychology approach posits. Therefore, positive psychology reinforces action in the framework of CSR, which is so highly recommended in organizations and companies today.